Stable overexpression of DNA fragmentation factor in T-47D cells: sensitization of breast cancer cells to apoptosis in response to acetazolamide and sulfabenzamide - Bagheri, Fatemeh (Mol Biol Rep, 2014)
Alterations in expression of the DFF40 gene have been reported in some cancers. This study is an in vitro study of the therapeutic effects of gene transfer that lead to elevation in DFF40 expression within T-47D cells in the presence of sulfonamide drugs. In this study, we have constructed a eukaryotic expression vector for DFF40 and transfected it into T-47D cancer cells. We used real time RT-PCR to detect the expression of DFF40 and the MTT assay to determine effects of the sulfonamide drugs acetazolamide, sulfabenzamide, sulfathiazole and sulfacetamide on cell viability in the presence of increased and normal DFF40 levels. Cell cycle distribution was assessed by propidium iodide (PI) staining and the rates of apoptosis by annexin V/PI staining. The DNA laddering analysis was employed to evaluate apoptosis. We observed that overexpression of DFF40 was only effective in decreasing viability in cells incubated with acetazolamide and sulfabenzamide. There was enhanced apoptosis in these groups, particularly with acetazolamide. The cell cycle distribution analysis showed that in the presence of sulfonamide drugs there were no substantial changes in empty-vector or DFF40-transfected cells, except for those cells treated with sulfabenzamide or sulfathiazole. There was no DNA laddering in cells that expressed the empty vector when incubated with sulfonamide drugs. In contrast, we observed DNA laddering in cells that expressed DFF40 in the presence of acetazolamide. Our results have demonstrated that combinatorial use of some sulfonamides such as acetazolamide along with increased expression of DFF40 can potently kill tumor cells via apoptosis and may be beneficial for treatment of some chemoresistant cancers.